ACHIEVING SUSTAINABILITY IN COUNTRIES WITH ECONOMIES IN TRANSITION: NEW OPPORTUNITIES AND PROSPECTS - Aubakirova, G.; Rudko, G.; Vyzhva, S.; Portnov, V.; Isatayeva, F.; Zimanovskaya, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article examines Kazakhstan, the largest economy in Central Asia, which, on the way to sustainable economic growth, adequately responds to systemic challenges and adapts the experience of advanced countries. The generalizing indicators of the effectiveness of state regulation of the processes contributing to the growth of the stability of the national economy are given. The reasons for the weak involvement of entrepreneurs and citizens in measures for the sustainable development of Kazakhstan have been identified. It has been substantiated that the development of a strategy for the country's sustainable development and the achievement of inclusive economic growth require coordination of the work of government bodies, business and civil society. It is shown that in Kazakhstan the main drivers for the implementation of the culture of sustainable development are large enterprises and the quasi-public sector. Private enterprises do not yet see the opportunity to profit from integrating sustainable development goals into business processes. The paper emphasizes that in order to increase the stability of the poorly diversified economy of Kazakhstan, emphasis should be placed on the transformation of the mining sector, which has the potential to maintain investment attractiveness, both for domestic and foreign investors. Based on the results of the study, the authors highlight the most important aspects of building a new model of sustainable development in the foreseeable future.
Keywords: transition economy; Kazakhstan; state regulation; sustainability; investment; mining industry